2020
DOI: 10.1104/pp.20.00859
|View full text |Cite
|
Sign up to set email alerts
|

MYB30 Orchestrates Systemic Reactive Oxygen Signaling and Plant Acclimation

Abstract: Systemic acquired acclimation (SAA) is a key biological process essential for plant survival under conditions of abiotic stress. SAA was recently shown to be controlled by a rapid systemic signaling mechanism termed the reactive oxygen species (ROS) wave in Arabidopsis (Arabidopsis thaliana). MYB30 is a key transcriptional regulator mediating many different biological processes. MYB30 was found to act downstream of the ROS wave in systemic tissues of Arabidopsis in response to local high light (HL) stress trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 36 publications
1
78
0
Order By: Relevance
“…3A). Analysis of transcript expression in local and systemic tissues of these mutants, in response to a local HL stress treatment, revealed that the steady-state level of different acclimation transcripts such as ZAT10 and ZAT12 ( 6, 9, 20, 21 ) was enhanced in local leaves (that were directly subjected to the HL treatment) of all mutants. With the exception of glr3.3glr3.6 , that displayed suppressed expression of acclimation transcripts in systemic leaves, the expression of ZAT10 and ZAT12 in systemic tissues of all other mutants was repressed (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3A). Analysis of transcript expression in local and systemic tissues of these mutants, in response to a local HL stress treatment, revealed that the steady-state level of different acclimation transcripts such as ZAT10 and ZAT12 ( 6, 9, 20, 21 ) was enhanced in local leaves (that were directly subjected to the HL treatment) of all mutants. With the exception of glr3.3glr3.6 , that displayed suppressed expression of acclimation transcripts in systemic leaves, the expression of ZAT10 and ZAT12 in systemic tissues of all other mutants was repressed (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…( B ) Real-time quantitative PCR analysis of transcript expression in local and systemic leaves of wild-type and the glr3.3glr3.6, cngc2, msl2,pip2;1 and pdlp5 mutants subjected to a local 0, 2 or 10 min HL treatment. Transcripts tested ( ZAT12, ZAT10, MYB30 ) were previously found to respond to HL stress at the local and systemic leaves of wild-type plants ( 6, 9, 20, 21 ). Results, expressed in RQ (relative quantity), were obtained by normalizing relative transcript expression and comparing it to control wild type from local leaf.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations